2008
DOI: 10.1002/prot.21927
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous asparaginyl deamidation of canine milk lysozyme under mild conditions

Abstract: Asparaginyl deamidation is a common form of nonenzymatic degradation of proteins and peptides. As it introduces a negative charge spontaneously and irreversibly, charge heterogeneity can be accumulated in protein solution during purification, preservation, and experiments. In this study, canine milk lysozyme (CML), a useful model for the study of the molten globule state, exhibited charge heterogeneity after sample purification. Four Asn residues in CML deamidated rapidly under mild conditions: pH 8.0 and 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Equine b-casein and equine a-la undergo spontaneous deamidation under physiological conditions at Asn 135 -Gly 136 and Asn 45 -Gly 46 , respectively (Girardet et al, 2006(Girardet et al, , 2004 which has been reported also for canine milk Lyz (Nonaka et al, 2008) and human Lf (Belizy et al, 2001) but not, to our knowledge, for bovine or human b-casein. Recent research has demonstrated that temperature may be an important factor controlling the spontaneous deamidation process and at 10 C the phenomenon is strongly reduced (Matéos et al, 2009a(Matéos et al, , 2009b.…”
Section: B-caseinmentioning
confidence: 79%
“…Equine b-casein and equine a-la undergo spontaneous deamidation under physiological conditions at Asn 135 -Gly 136 and Asn 45 -Gly 46 , respectively (Girardet et al, 2006(Girardet et al, , 2004 which has been reported also for canine milk Lyz (Nonaka et al, 2008) and human Lf (Belizy et al, 2001) but not, to our knowledge, for bovine or human b-casein. Recent research has demonstrated that temperature may be an important factor controlling the spontaneous deamidation process and at 10 C the phenomenon is strongly reduced (Matéos et al, 2009a(Matéos et al, , 2009b.…”
Section: B-caseinmentioning
confidence: 79%
“…The protein unfolds, exposing regions that are normally protected, which then immediately aggregate to decrease surface exposure of these hydrophobic residues. Previous reports (48) have shown that secondary structure formation prevents Asn from deamidation due to restrained flexibility of local structure, which might provide an explanation for the low levels of deamidation observed only at solvent-exposed Asn residues in the 65C/pH 8.5 stressed sample. In contrast, many Asn residues are extensively deamidated in the 90C stressed sample because of the most extreme disruption of protein secondary and tertiary structures.…”
Section: Discussionmentioning
confidence: 96%
“…These structural changes may lead to exposure of new residues, making additional sites susceptible to deamidation, as has been shown for ribonuclease A in vitro (Zabrouskov et al 2006). However, since deamidation can occur even under mild conditions in vitro (Nonaka et al 2008), the use of high pH and high temperature may artifactually introduce deamidation. The purpose of the experiments in this study was to determine which physiological deamidation sites have the greatest affect on structure and stability as a first step in determining the overall relevance of deamidation during aging and cataracts.…”
mentioning
confidence: 99%